1998
DOI: 10.2165/00019053-199813020-00008
|View full text |Cite
|
Sign up to set email alerts
|

Cost of an Outbreak of Hepatitis A in Puglia, Italy

Abstract: In total, 5889 cases of hepatitis A virus infection were reported during an outbreak in Puglia, a region of Southern Italy, in 1996. The primary cause of the outbreak was consumption of contaminated food (raw shellfish, vegetables, etc.), with a contributory risk factor of person-to-person transmission. A detailed questionnaire was completed by 250 randomly selected patients to obtain information sufficient to calculate the direct and indirect costs of the outbreak for the individual patient, the National Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 13 publications
0
14
0
2
Order By: Relevance
“…21,22 Recently, the economic burden of a community-wide hepatitis A outbreak was calculated in Puglia, Italy. 23 Costs were calculated to be 662 US $ for the individual patient, whereas total societal costs amounted to 24.45 million US $ for the 5,889 cases of hepatitis A monitored during this outbreak in Italy. Currently, a study surveying mortality and morbidity caused by hepatitis A virus infections is ongoing and a health economics study is planned in several Latin American countries.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Recently, the economic burden of a community-wide hepatitis A outbreak was calculated in Puglia, Italy. 23 Costs were calculated to be 662 US $ for the individual patient, whereas total societal costs amounted to 24.45 million US $ for the 5,889 cases of hepatitis A monitored during this outbreak in Italy. Currently, a study surveying mortality and morbidity caused by hepatitis A virus infections is ongoing and a health economics study is planned in several Latin American countries.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalization costs accounted for 91.4% of total treatment costs, a higher percentage than that found in previous studies (61-84%) (Lucioni et al 1998;Bownds et al 2003;Sansom et al 2003). Thus, attention must be paid to the fact that recent service utilization of patients with hepatitis A has centered on inpatient care and that total treatment costs are increasing due to the increase in hospitalization costs.…”
Section: Discussionmentioning
confidence: 91%
“…Reliable analyses of treatment costs or economic burden are necessary to develop an appropriate disease management strategy for hepatitis A. Although studies analyzing the economic burden or the treatment costs for hepatitis A have been conducted in some developed countries (Dalton et al 1996;Demicheli et al 1996;Lucioni et al 1998;Bownds et al 2003;Sansom et al 2003;Artega et al 2009), most are not representative, because they used partial data from specific locations or medical institutions rather than nationwide data. Moreover, those studies conducted a limited analysis of medical service utilization and treatment costs associated with the characteristics of patients.…”
mentioning
confidence: 99%
“…Although this is true also for Italy as a whole, as documented by both notification (Mele et al, 2006;ISTAT, 1980ISTAT, -2006 Italy, where a very large outbreak was observed in 1996-1997 (Lucioni et al, 1998), despite the improvement of socio-economic conditions.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Nevertheless, viral hepatitis A represents an important public health issue, imposing a remarkable economic burden worldwide (Berge et al, 2000;Das, 2003) and in Italy as well (Lucioni et al, 1998).…”
Section: Introductionmentioning
confidence: 99%